2017
DOI: 10.1017/dmp.2017.123
|View full text |Cite
|
Sign up to set email alerts
|

Dallas MegaShelter Medical Operations Response to Hurricane Harvey

Abstract: On August 25, 2017, Hurricane Harvey made landfall near Corpus Christi, Texas. The ensuing unprecedented flooding throughout the Texas coastal region affected millions of individuals.1 The statewide response in Texas included the sheltering of thousands of individuals at considerable distances from their homes. The Dallas area established large-scale general population sheltering as the number of evacuees to the area began to amass. Historically, the Dallas area is one familiar with "mega-sheltering," beginnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Thousands of Houston residents evacuated, many to the DFW metroplex. 10,11 Harvey ultimately caused 88 deaths and an estimated US $125 billion of damage, making it the second-costliest tropical cyclone in US history, following Hurricane Katrina. 12 During disasters of Hurricane Harvey's scale, hospitals are among the first institutions impacted, and, as such, they are often faced with a surge in demand for medical services that can overwhelm their resources.…”
Section: Introductionmentioning
confidence: 99%
“…Thousands of Houston residents evacuated, many to the DFW metroplex. 10,11 Harvey ultimately caused 88 deaths and an estimated US $125 billion of damage, making it the second-costliest tropical cyclone in US history, following Hurricane Katrina. 12 During disasters of Hurricane Harvey's scale, hospitals are among the first institutions impacted, and, as such, they are often faced with a surge in demand for medical services that can overwhelm their resources.…”
Section: Introductionmentioning
confidence: 99%
“…19 Those patients may have sought care in more accessible facilities such as smaller, freestanding EDs or UCCs, or clinics that were operating within or near shelters. 11,20,21 This possible explanation is supported by a study from the closest major metropolitan area that reported an 11% increase in ED visits in the Dallas-Fort Worth area in the month following Hurricane Harvey, with an associated increase in patients who reported residing in the metro Houston area and presented with chief complaints that included the words "hurricane," "Harvey," "evacuee," or "evacuate." 22 A similar decrease in total ED patient visits at a large county hospital in the metro Houston area in the four weeks following Hurricane Harvey was noted.…”
Section: Discussionmentioning
confidence: 92%
“…Planning facilities for JP in advance before FSH construction FSH has the task of undertaking large-scale natural disaster rescue and mass infectious disease treatment. It played a critical role in disaster relief after several natural disasters and early stage of resistance to COVID-19 [17]. However, the Omicron wave in Shanghai infected tens of thousands of people, and there were a large number of people in the FSH.…”
Section: Discussionmentioning
confidence: 99%